Sustainability and Privilege : A Critique of Social Design Practice - Arboleda, Gabriel (Book collections on Project MUSE., 2022)
"With "sustainability" becoming an ever-less-meaningful buzzword in design disciplines over the past couple of decades, it's both shocking and bracing to see Gabriel Arboleda employ the term as a near-pejorative in light of what he sees as its implications of cutural imperialism and class oppression. In "Sustainability and Privilege," he contends, "Sustainability can be invoked for the marginalization and displacement of vulnerable populations through projects that involve experimentation of faulty alternative technologies, or that result in so-called green gentrification, or that impose economic and other burdens on these populations." Arboleda is fiercely critical of the way "social design" has been carried out in impoverished regions of the world, most notably Africa and Latin America. Importantly, he doesn't just criticize: he is prescriptive, proposing new approaches to social design and arguing for a simpler, more transparent, and more stakeholder-involved design process that will eliminate the casual imposition of the architect's ideas on vulnerable populations"--